Emergence of ISO 9001:2015 standard and its linkage with world class manufacturing strategies. (11th May 2021) - Santhose, M.; Senthil, V.; Devadasan, S.R.; Balakrishnan, K.
Right from the days of their release, ISO 9000 series standards-based quality management system (QMS) has been implemented in large number of organisations. Whenever revisions were made, organisations tuned their QMS to adhere to the respective revised version of ISO 9000 series standards. This kind of need has arisen now due to the release of ISO 9001:2015 standard. In the context of observing this need, the survey reported in this paper was carried out with the objective of exploring the nuances of ISO 9001:2015 standard and its implementation trend in organisations. The results of this survey have indicated that the organisations are now slowly turning their QMS to adhere to the stipulations of ISO 9001:2015 standard. Further, in this article, the need of integrating 'total productive maintenance' (TPM) with the ISO 9001:2015 standard-based QMS is pointed out. This article is concluded by claiming that such integration and its implementation will enable the modern organisations to attain world class manufacturing goals.